Doświadczenie historyczno-religijnej alienacji a współczesne relacje wewnątrz chrześcijaństwa Moskałyk Jarosław - Moskałyk, Jarosław (Poznańskie Studia Teologiczne, 2013)
The problem of unity within the Christian and interreligious rapprochement is in its essence complex and multifaceted. The attempt to look at this issue through the experience of the alienation complex wishes to cast some light on the factors that in principle exclude the possibility of reconciliation. The phenomenon of alienation in interdenominational relations is very often overlooked, and its consequences are hastily hushed up. However, a proper assessment of the situation of alienation in mutual relations between churches or religions should be a simple gesture of courage and willingness to make a change. Yet, this is not simple, all the more so when done at someone else’s request. It is still a long way to catharsis and a sense of fellowship with others, but this is what the Catholic Church and the entire Christianity needs. A genuine attitude of openness, ecumenical openness included, is what the Christian community is called to in order to perform its specific missions in the contemporary world.